Shunt active power filter control based on Z-source inverter fed by PV system - Abdelkarim, Ahfouda; Youcef, Bekakra; Toumi, Djaafar; Ibrahim, Ahmed; Zellouma, Laid; Messaoud, Hettiri (Institute of Advanced Engineering and Science, 2024)
In this paper, an integration of a Z-source inverter (ZSI)-based shunt active power filter (SAPF) fed by a photovoltaic (PV) system for the enhancement of power quality is proposed. The ZSI provides substantial advantages including improved boost functionality, reduced harmonics, and superior performance compared to traditional inverters. In this paper, the SAPF control is based on instantaneous reactive power theory. A proportional-integral (PI) controller is implemented for DC-link voltage control, with the primary aim of this study being the elimination of total harmonic distortion (THD) in the source current. To demonstrate the effectiveness of the proposed approach, simulations were conducted using MATLAB/Simulink across various operating conditions. The outcomes substantiate and validate the efficacy of the proposed method.